2020
DOI: 10.1016/j.anai.2020.07.013
|View full text |Cite
|
Sign up to set email alerts
|

The origins of allergy from a systems approach

Abstract: Allergy in its various manifestations is a systems disease consisting of networks among multiple organs. The epithelium plays a central role in allergic disorders, and allergic sensitization occurs through the skin unless tolerance is induced through the gastrointestinal tract. Filaggrin loss-of-function mutations result in impaired epithelial barrier integrity and are substantial genetic risk factors for atopic dermatitis, asthma, allergic rhinitis, and food allergy in children. Dysregulated growth and repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 101 publications
0
30
0
2
Order By: Relevance
“…Conversely, introduction of foods via the gut leads to induction of regulatory T-cells (Tregs) and tolerance to potential food allergens. 27 28 29 It is well known that Tregs are important in the immune system for maintaining tolerance. Cord blood studies have demonstrated that even at birth, the infants who eventually develop FA had lower Tregs and higher inflammatory cytokines.…”
Section: Gut Function As a Tolerizing Organmentioning
confidence: 99%
“…Conversely, introduction of foods via the gut leads to induction of regulatory T-cells (Tregs) and tolerance to potential food allergens. 27 28 29 It is well known that Tregs are important in the immune system for maintaining tolerance. Cord blood studies have demonstrated that even at birth, the infants who eventually develop FA had lower Tregs and higher inflammatory cytokines.…”
Section: Gut Function As a Tolerizing Organmentioning
confidence: 99%
“…38 In this, an increasingly important role is recognized in the components of exposome including allergen contacts, environmental pollution, intestinal and skin microbiome. 39,40 In most people, the ingestion of food determines the development of immunological tolerance. This process, particularly active in the first months of life, depends on the amount of foods reaching the bowel, the intestinal permeability, the endocytic capacity of the enterocytes, and the immune response of intestinal cells and the whole organism.…”
Section: Med Iator S Involved In Food Allergymentioning
confidence: 99%
“…On a genetically predisposed terrain, 37 the inception of the disease depends substantially on environmental factors which determine the transcription or not of genes leading towards the creation of specific IgE 38 . In this, an increasingly important role is recognized in the components of exposome including allergen contacts, environmental pollution, intestinal and skin microbiome 39,40 …”
Section: Mediators Involved In Food Allergymentioning
confidence: 99%
“…However, in certain individuals with a genetic and environmental predisposition (e.g., altered microbiota, viral or bacterial infection, chemicals additives, or pollutants), regulation of intestinal inflammation is impaired leading to chronic relapsing immune activation against luminal antigens IBD, food allergy and Coeliac disease. [ 68–71 ]…”
Section: Gate Keepers Of Intestinal Immune Tolerance and The Role Of mentioning
confidence: 99%
“…However, in certain individuals with a genetic and environmental predisposition (e.g., altered microbiota, viral or bacterial infection, chemicals additives, or pollutants), regulation of intestinal inflammation is impaired leading to chronic relapsing immune activation against luminal antigens IBD, food allergy and Coeliac disease. [68][69][70][71] Luminal antigens are sampled by the antigen presenting cells (APCs), mainly dendritic cells (DCs) and macrophages in the lamina propria. Instead of inducing an inflammatory reaction to these antigens, the mucosal APCs in a healthy gut travel to the gut associated lymphoid tissues and to the mesenteric lymph nodes where they initiate a regulatory adaptive immune response to unharmful food and microbial antigens mainly via the induction of antigen specific T regulatory cells expressing Foxp3.…”
Section: Gate Keepers Of Intestinal Immune Tolerance and The Role Of mentioning
confidence: 99%